PENGARUH PENGGUNAAN GADGET TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK SEKOLAH DASAR - Sulistia Ningsih; Arsan Shanie (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2023)
The use of gadgets nowadays has penetrated into the word of education including in elementary schools. Many parents facilitate their children who are still in elementary school with gadgets for learning media, communication tools, play tools, and to please children. However, these reasons ore not always good. Children will think that gadgets are everything for them. So that these conditions certainly have an impact on children's critical thinking skills. The purpose of this study was to see the effect of using gadgets on the critical thinking skills of grade 6 students at Madarah Ibtidaiyah Nashrul Fajar Meteseh Tembalang. This type of research uses quantitative methods with an ex post facto design. A total of 32 class 6 students were used as research subjects. Observation, questionnaires, tests, and documentation were used as data collection methods. The data analysis method used is the prerequisite test analysis, which consists of a normality test and a linearity test, with a hypothesis test as the final analysis. From the results of statistical analysis tests using SPSS 26 software using the t statistical test, the results obtained are t_count = 3.115 and t_table = 2.042. So that t_count ˃ t_table is 3.115 ˃ 2.042. So H0 is rejected, meaning that variable X (use of gadget) has a significant effect on variable Y (critical thinking skills). So it can be stated that the usage of gadgets is one among the factors influencing the critical thinking abilities of class 6 students at Madrasah Ibtidaiyah Nashrul Fajar Meteseh Tembalang